Pengaruh gadget terhadap perkembangan anak - Fitriani, Cici; Hasiah, Hasiah; Amaluddin, Zainal; Nurhakim, Lukman (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The aim of the study was to find out how devices influence the emotional development of early childhood; discussions suggested that the use of devices against early children has a significant negative impact on the child's emotional and social development will be inhibited, including mental disorders, unstable emotions, and emotional relationships between parents and children. In this research the author obtains information data in the study of libraries, library studies is a way to collect information and data from various sources such asbooks, journals, articles and others. Almost all kinds of research requires library study, in each library search research that is mainly and is included as an initial step to prepare a research framework.